Erratum to: Beyond Acclamations and Excuses: Environmental Performance, Voluntary Environmental Disclosure and the Role of Visibility - Dawkins, Cedric E.; Fraas, John W. (2011)
Some researchers have argued that firms with favorable environmental performance are more likely to provide voluntary environmental disclosure, while others have argued that firms with poor environmental performance are most likely to disclose. The authors propose a curvilinear relation between environmental performance and environmental disclosure that is moderated by visibility. Data were obtained from S&P 500 firms queried by Ceres’ Climate Disclosure Project. Results show a U-shaped environmental performance–environmental disclosure relation and a main effect for visibility but no moderating effect for visibility on the U-shaped environmental performance–environmental disclosure relation. The authors discussed the implications of these results for future research and practice.
Keywords: voluntary environmental disclosure; Corporate social responsibility disclosure; Environmental Disclosure; Disclosure; Corporate Social Responsibility